Pemberdayaan Usaha Kecil dan Menengah Melalui Penyuluhan Kewirausahaan di Kelurahan Pondok Kacang Timur - Qodariah Qodariah; Etty Susilowaty; Widi Wahyudi; Fathin Aulia Rahman; Marsin Marsin; Hari Subagio; Imam Tri Wibowo (Pusat Riset dan Inovasi Nasional, 2025)
The Indonesian economy faces the challenges of economic inequality and high unemployment. One solution is the development of local entrepreneurship through the empowerment of Small and Medium Enterprises (SMEs). This Community Service Program (PKM) aims to increase the entrepreneurial capacity of the community in Pondok Kacang Timur Village through counseling on business plans, business legality, marketing, and financial management, with a focus on the use of information technology for operational efficiency. The counseling program demonstrated high participation from SMEs, with significant improvements in understanding aspects of business plans, business legality, and marketing. However, some participants still faced obstacles in implementing technology, particularly in financial management using accounting information systems. The positive impacts of this activity include improved entrepreneurial skills, which are expected to expand markets and increase SME income, as well as empower the local economy through the creation of business opportunities and reduced unemployment. However, ongoing mentoring is still needed to maximize the potential of SMEs through the application of technology.